Building OptiPath: A Cloud-Based system for Optimal Route Calculation using ArcGIS Enterprise - H. Wang; H. Wang; D. Jain; J. Greenspon; J. Greenspon; J. Blossom (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This research presents OptiPath, a system tailored for optimizing route planning within big geospatial data projects. By harnessing extensive raster data and leveraging cloud computing resources, OptiPath excels in spatial analysis and path optimization for com- plex geospatial applications. In a project involving a historical U.S. pipeline simulation, OptiPath generated 8 optimal paths, each processing 2.50 GB of raster data in an average time of 10 minutes per path. Consequently, the system efficiently processed 20GB of raster data within 1.5 hours. OptiPath accurately computes optimized paths between specified origins and destinations based on user input, aligning closely with actual routes in a time and cost-effective manner. This system’s outstanding performance makes it an asset for diverse and complex route planning projects. OptiPath operates on the New England Research Cloud (NERC), running on Esri’s ArcGIS Enterprise software. Beyond offering an effective, efficient routing solution, OptiPath underscores the immense potential of integrating cloud computing and ESRI’s big data tools for GIS applications.